Antiretroviral Drug Concentrations in Hair Are Associated with Virologic Outcomes Among Young People Living with HIV in Tanzania - Tabb, Zachary J. (AIDS, 2018)
OBJECTIVE: We assessed the relationship of self-reported adherence versus antiretroviral therapy (ART) concentrations in hair with virologic outcomes among young people living with HIV. DESIGN: This was a cross-sectional study that enrolled young people living with HIV age 11–24 years, who attended a youth HIV clinic in Moshi, Tanzania. METHODS: ART adherence was assessed by self-report, drug concentration in hair samples, and plasma HIV-1 RNA measurements. Those with virologic failure, defined as plasma HIV-1 RNA > 400 copies/mL, had genotypic resistance assessed. Receiver operating characteristic (ROC) curves were used to evaluate ART-concentration threshold cut-offs for virologic suppression, after excluding those with known high-level resistance mutations. RESULTS: Among 280 young people enrolled, 227 were included in the final analysis. Seventy-two (32%) self-reported inadequate adherence and 91 (40%) had virologic failure. Hair ART-concentration (p<0.001), but not self-reported adherence (p=0.53), was associated with virologic outcome. Sixty-seven (74%) of those with virologic failure had resistance testing performed, of whom60% had high-level resistance. ROC curves demonstrated moderate or high classification performance for association with virologic suppression with specific hair ART-concentration cut-offs for lopinavir (1.8ng/mg), efavirenz (1.04 ng/mg), and nevirapine (33.2 ng/mg). CONCLUSIONS: Hair ART-concentrations were significantly associated with virologic outcomes among young people living with HIV. ART-concentration thresholds associated with virologic suppression are proposed. Hair analysis may provide a non-invasive, cost-effective adherence assessment tool in settings with limited 2(nd) and 3(rd)-line treatment options.